PENGELOLAAN DATA PENELITIAN DI PERPUSTAKAAN: TANTANGAN DAN PERSIAPANNYA BAGI PUSTAKAWAN - Wahid Nashihuddin (Perpustakaan Nasional RI, 2020)
Research data management will become a new service trend for libraries and new jobs for librarians. Libraries and librarians need to prepare their organizational resources to support the library-data services. Various challenges and efforts need to be prepared from an early age so that research data management in the library can be carried out properly. This study discusses the management of research data in libraries, the challenges and efforts of librarians in managing institutional research data. The research objectives are to determine: (1) library institutions that have carried out research data management and services; (2) challenges and efforts of librarians in managing institutional research data. This research uses a qualitative approach. The research data comes from literature studies, especially scientific journal articles (national and international). Data analysis was carried out descriptively with the stages, are planning, conducting, and reporting. Based on this method, the results of the study indicate that: (1) research data management has been carried out in various libraries in Indonesia, and in its application it can adopt the concept of data libraries at the University of Toronto Map and Digital Library (UTMDL) Canada; (2) In managing institutional research data, librarians will face various problems and challenges, both in terms of policy implementation and increasing competence in research data management.